Protein Content and Acceptability of Nutrient Dense Noodles Based on Local Food as an Alternative to Emergency Food - Irma Eva Yani; Vinny Pratiwi; Marni Handayani (proceedinginternational, 2023)
Noodles are foods that are accepted by all levels of society, including adults and children. There are various types of noodles, one of which is wet noodles. Wet noodles are high in carbohydrates, but low in protein. Noodles that are usually sold in the market require 8.4 grams of additional protein to comply with SNI, which is a minimum of 9.0 grams of protein in 100 grams of wet noodles. So it is necessary to add dried rebon shrimp flour as a protein source. The purpose of the study was to determine the protein contentand acceptability of wet noodles substituted with dried rebon shrimp flour. The type of research is experimental research in the field of food technology with a completely randomized design (CRD) one control, three treatments, two repetitions. Test of protein content in the Baristand Padang laboratory and acceptance test at SDN 10 Surau Gadang. The study was conducted from March 2020 to April 2021. The best treatment was obtainedby organoleptic testing. The results of the organoleptic test obtained the best treatment with a ratio of 75:25 grams, 8.1% protein content and as much as 80% of the target can spend the product. It is recommended to do a acceptability test after a laboratory test, as well as conduct a food safety test.